Sensitivity Improvement of A Direct Competitive Elisa for Atrazine by Exploiting Low Cross-Reactivity of An Atrazine-Specific Recombinant Antibody Fab-Fragment - Kusharyoto, Wien; Schmid, Rolf D. (ANNALES BOGORIENSES, 2004)
The hapten-binding site of the antibody Fab-fragment K411 B specific towards the herbicide atrazine (2-cllloro-4-(ethylamino)-6-(isopropyJamjno)- 1,3,5-triazine) was modified by means of structural modeling and site-directed mutagenesis. A triple mutant (GlnL89GlulValH3711e/GluL3Val) of the Fab-fragment showed an increased affinity towards the hapten HlCVC6 (4-arnino-6-chloro-l ,3,5-triazine-2-(6-aminohexanecarboxylic acidÂ» compared to the affinity ofthe wild-type Fab-fragment lowards the same hapten. However, the mutant exhibited substantially lower affinity towards the hapten H/CVC6 Ihan towards atrazine and the hapten iPr/ CVC6 (4-chloro-6-(isopropylamino)-1,3,5-triazioe-2-(6-aminohexanecarboxylic acidÂ», which is usual ly used in the synthesis of enzyme tracers in ELISA for atrazine. Advantage was taken of the low cross-reactivity and increased affinity of the mutant Fab fragment towards H/CVC6 to improve the sensitivity of a direct-competitive ELISA tor atrazine. HlCIlC6 was covalently conjugated with horseradish peroxidase (HRP), and the conjugate H/CI/C6-HRPwas used as enzyme tracer in the ELISA for atrazine. An eight-fold improvement in sensitivity ofa direct-competitive ELISA for atrazine could be achieved using the tracer H/CVC6-HRP compared to the sensitivity of ELISA using the tracer iPr/CVC6-HRP. The detection limit for atrazine was as low as 0.01 i g/l.Â